#### Answer

$\begin{align*}
\text{Sum: }&
2
\\\\
\text{Product: }&
1
\end{align*}$

#### Work Step by Step

Given the quadratic equation $ax^2+bx+c=0,$ the sum and product of its roots are given by the following ratios:
\begin{align*}
\text{Sum: }&-\dfrac{b}{a}
\\\\
\text{Product: }&\dfrac{c}{a}
.\end{align*}
Hence, the sum and product of the roots of the given equation, $
x^2-2x+1=0
,$ are
\begin{align*}
\text{Sum: }&-\dfrac{-2}{1}
\\&=
2
\\\\
\text{Product: }&\dfrac{1}{1}
\\&=
1
.\end{align*}